In vivo biocompatibility and biodegradation of a novel thin and mechanically stable collagen scaffold. Issue 4 (8th August 2013) - Rahmanian‐Schwarz, Afshin; Held, Manuel; Knoeller, Tabea; Stachon, Susanne; Schmidt, Timo; Schaller, Hans‐Eberhard; Just, Lothar
Abstract The demand for scaffolds comprised of natural materials such as collagen has increased in recent years. However, many scaffolds rely on chemical or physical modifications in order to comply with the necessary requirements for biomedical engineering. We evaluated the in vivo biocompatibility and biodegradation of a novel, thin, mechanically stable, and chemically non‐crosslinked collagen cell carrier (CCC). CCC was implanted subcutaneously into 25 adult Lewis rats and biopsies were taken on days 7, 14, 21, 42, and 84 after surgery. For histological analysis, paraffin sections of implanted skin were immunolabeled for CD68 and stained by hematoxylin–eosin and Masson–Goldner's trichrome method. Macroscopic analysis of skin surface during wound healing process showed a normal physiological reaction. Biodegradation of CCC was completed 42 days after subcutaneous implantation. Histological evaluation revealed no evidence of encapsulation, scar formation, or long‐term vascularization and inflammation. The collagen type I based biomaterial demonstrated a high in vivo biocompatibility, low irritability, complete resorption, and replacement by autologous tissue. The in vivo biocompatibility and degradation behavior encourage for further evaluation of CCC in surgical applications and regenerative medicine. © 2013 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 102A: 1173–1179, 2014.